Peran dan Kontribusi Pajak Reklame terhadap Pendapatan Asli Daerah Kabupaten Asahan - Lubis, Putri Kemala Dewi; Suhendra; Manik, Elisabeth Fitryany; Zahar, Muhamad Abdul (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Advertisement tax makes a significant contribution to increasing Asahan Regency's original regional income. Therefore, this research aims to discuss in depth the role of advertising tax on Original Regional Income in Asahan Regency and identify its potential impact on development and progress of the local area. The method used in this research uses quantitative descriptive research methods. The type of data used in this research is secondary data originating from the Central Statistics Agency (BPS) in the period 2016 to 2020 regarding the realization of regional tax revenues and the realization of Regional Original Income (PAD) revenues in Asahan Regency. The results of data analysis show that the role and contribution of advertising tax is very lacking in Asahan Regency's Original Regional Income (PAD). It can be seen from the contribution figures, namely in 2016 it was 2.06%, in 2017 it was 1.86%, in 2018 it increased by 2.30%, in 2019 it was 1.81%, and in 2020 it was 0.30%.